A Survey of Chinese Pig Farms and Human Healthcare Isolates Reveals Separate Human and Animal Methicillin‐Resistant Staphylococcus aureus Populations. Issue 4 (11th December 2021) - Zou, Geng; Matuszewska, Marta; Jia, Ming; Zhou, Jianwei; Ba, Xiaoliang; Duan, Juan; Zhang, Caishi; Zhao, Jian; Tao, Meng; Fan, Jingyan; Zhang, Xiangming; Jin, Wenping; et al.
Abstract: There has been increasing concern that the overuse of antibiotics in livestock farming is contributing to the burden of antimicrobial resistance in people. Farmed animals in Europe and North America, particularly pigs, provide a reservoir for livestock‐associated methicillin‐resistant Staphylococcus aureus (LA‐MRSA ST398 lineage) found in people. This study is designed to investigate the contribution of MRSA from Chinese pig farms to human infection. A collection of 483 MRSA are isolated from 55 farms and 4 hospitals in central China, a high pig farming density area. CC9 MRSA accounts for 97.2% of all farm isolates, but is not present in hospital isolates. ST398 isolates are found on farms and hospitals, but none of them formed part of the "LA‐MRSA ST398 lineage" present in Europe and North America. The hospital ST398 MRSA isolate form a clade that is clearly separate from the farm ST398 isolates. Despite the presence of high levels of MRSA found on Chinese pig farms, the authors find no evidence of them spilling over to the human population. Nevertheless, the ST398 MRSA obtained from hospitals appear to be part of a widely distributed lineage in China. The new animal‐adapted ST398 lineage that has emerged in China is of concern. Abstract : Zoonotic transmission of methicillin‐resistant Staphylococcus aureus (MRSA) is a significant problem and adds to the burden on antibiotic resistance in human healthcare. However, population‐level genomic studies reveal a separate MRSA population between farmed pigs and people in central China, a high pig farming density area.